1980
DOI: 10.1084/jem.151.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Role of antigen-presenting cells in the development and persistence of contact hypersensitivity.

Abstract: Three outcomes pertinent to contact sensitivity (CS) follow immunization with various forms of trinitrophenylated (TNP) substrates: (a) specific immunological unresponsiveness for CS is induced when immunization favors activation of splenic suppressor cells. This state is achieved by intravenous injection of trinitrophenyl-conjugated to various types of cells, such as peritoneal exudate cells (PEC). (b) A short-lived or evanescent form of CS is induced when immunization reduces activation of the suppressor cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(65 citation statements)
references
References 17 publications
4
61
0
Order By: Relevance
“…However, in the relative absence of an essential Cy-sensitive cell in the suppressor T-cell circuit, pre-TDH effector cells will be activated. This observation in some respects is very similar to the recent findings of Ptak et al (26). These investigators observed in the trinitrophenol contact sensitivity system, that intravenous injection of hapten-coupled cells will preferentially activate suppressor T cells as shown previously (23,27).…”
Section: Discussionsupporting
confidence: 81%
“…However, in the relative absence of an essential Cy-sensitive cell in the suppressor T-cell circuit, pre-TDH effector cells will be activated. This observation in some respects is very similar to the recent findings of Ptak et al (26). These investigators observed in the trinitrophenol contact sensitivity system, that intravenous injection of hapten-coupled cells will preferentially activate suppressor T cells as shown previously (23,27).…”
Section: Discussionsupporting
confidence: 81%
“…Ptak et al (1980) found that antigen coupled to epidermal cells induced immunity when injected intravenously, whereas antigen coupled to peritoneal exudate cells induced specific immunological unresponsiveness. It is possible that in the absence of LC, tumour antigens may filter through the skin and be presented to lymphocytes by monocytes, resulting in unresponsiveness.…”
Section: Enumeration Of Lc In Epidermal Sheetsmentioning
confidence: 99%
“…Lyt23 ÷ cells are perhaps directly stimulated by replicated viral antigens and in infected mice they are the only effectors (Eardley et al, 1978). It is also possible that the Ts cells were induced as a result of Ia-positive macrophages being eliminated by infection with LDV (Ptak et al, 1980). Evidence for this was obtained when perfusion of Ia-positive peritoneal cells into LDV-infected mice significantly restored the DTH response to the immunizing virus (Unanue et al, 1984).…”
Section: Discussionmentioning
confidence: 90%